The Influence of Transformational Leadership Style, Organizational Climate and Work Discipline on Employee Performance - Abdul Basir (Yayasan Riset dan Pengembangan Intelektual, 2023)
Human resource is the executor of the various activities in an organization and has a very large role for the development of the organization. An organization has their own criteria in determining human resource qualification. Excellent employees will contribute significantly to achieve the organization's goals.This study aims to analyze the factors influencing employee performance at the PT FIF Group Branch of Selong, East Lombok. These factors include transformational leadership style, organizational climate and work discipline. The research used the quantitative with regression analysis method. The data was collected using questionnaires distributed to all employees of PT FIF Group Branch of Selong. The sampling method used is census sampling technique with a total population of 32 employees. The data were analyzed with IBM SPSS version 22 and analysis was carried out by several tests such as validity test, reliability test, classic assumption test, linear regression analysis and coefficient of determination test. The results of this study indicate that partially, transformational leadership style, organizational climate and work discipline have a positive and significant effect on employee performance. Simultaneously, transformational leadership style, organizational climate and work discipline have a positive and significant effect on employee performance at the PT FIF Group Branch of Selong.